The Benefits of Flipped Classroom Model for Efl Learners - Kristoforus Gustian; Desy Rusmawaty; Aridah Aridah (Journal on Education, 2023)
The flipped classroom model is an instructional strategy that is currently gaining popularity among educators and instructors. It differs from the traditional teaching approach, in which teachers primarily give instructions in classrooms. Before class, students are asked to watch video that contains the materials which are going to be discussed in class. The teacher then encourages them to participate actively in class and work together with their classmates. The advantages of applying FCM in the context of EFL learners have existed since its application in every field, however only few scholars discussed it with the limited aspect. The purpose of this study is to present the benefits of FCM for EFL learners through discussing the ideas proposed by some scholars that have seen some advantages via their research. The discussion focuses on the benefits in the context of EFL learner with some elaborations concerning the importance of FCM in education field with a short elaboration of the benefits for teacher as a part of the learning process.